PENGARUH BUDAYA MAHE SE KALFINO TERHADAP PERILAKU MEMBUANG SAMPAH SEMBARANGAN DI KELURAHAN SASA: Bahasa Indonesia - S Abd Latief, Nurulsani; Munadiyah, Siti; Soebagio, Dwirara (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Ternate City is known for its natural beauty and culture, but it also faces a serious waste problem. This study aims to understand the influence of the mahe se kalfino culture on littering habits in Sasa Village. The method used is a Mixed Method quantitative and qualitative with involving 110 respondents for quantitative data and 2 respondents for qualitative data, using simple random sampling. Data were obtained through questionnaires, and validity using Gregory's formula and reliability of the measuring instrument Alpha Cronbach were tested. The results showed no significant influence of the mahe se kalfino culture on littering habits (p = 0.264), influenced by the lack of facilities, frequency of waste collection, and low public awareness.. Keywords: Mahe se kalfino culture, littering behavior, fear and shame behavior